Farmers' Perceptions of Cashew Marketing Channels in North Wawonii District, Konawe Islands Regency - Embe; Ulmia (Fakultas Pertanian Universitas Muhammadiyah kendari, 2022)
This research was conducted in North Wawonii District, Konawe Islands Regency in January-February 2020. The aim of this study was to determine farmers' perceptions of cashew marketing channels in North Wawonii District, Konawe Islands Regency. The population in this study are farmers who cultivate cashew, totaling 320 people. The size of the sample is determined based on the slovin formula so that a sample of 39 people is obtained. Farmers' perceptions of each marketing channel are: Perceptions of the cashew price aspect for channel 1 disagree (TS), while for channel 2 strongly agree (SS), perceptions of the aspect of ease of reaching marketing channel channel 1 strongly agree (SS), while for channel 2 do not agree (TS), the perception of the capacity aspect for channel 1, farmers disagree (TS), while channel 2 strongly agree (SS).